Efektifitas Program Suplementasi Zat Besi pada Remaja Putri di Kota Bogor - Tyas Permatasari; Dodik Briawan; Siti Madanijah (Media Kesehatan Masyarakat Indonesia, 2018)
Prevalence of anemia in adolescent girl was still high. The iron supplementation program for improvingthe iron status, but this program is not always successfully to reducing prevalence anemia. The objective was toanalyzed factor that influenced succesfully of iron supplementation program at the adolescent girls. A quasi experimentpre-post intervention design was applied in female student at Bogor City between September 2016 untilJanuary 2017 run by the Health Office of Bogor City. A number of 172 adolescent girls (aged 10-18 years) participatedin the study from 4 school in Bogor City. Blood was collected through fingerthick and analyzed with cyanmethemoglobinmethod. The result showed that prevalence of anaemia (Hb <12g/dl) was found to be 20.7% anddecreased by 5.2% after four month of supplementation. The logistic regression analyses showed that status beforesupplementation was factor that affect improve of haemoglobin level (p<0.05;OR=3.52;CI95%=1.40-8.85). Theiron supplementation program in Bogor city did not effective.